Navigation and MIS in orthopedic surgery - Stiehl, James B. (Springer Berlin Heidelberg, 2007)
This textbook offers new insights into the use of computer assisted surgery and minimally invasive surgery in orthopaedic surgery. A comprehensive presentation of scientific work and clinical experience is included encompassing areas of spine, trauma, sports and reconstructive surgery. We have added sections that discuss minimally invasive surgery, as we believe CAS will be an enabling technology for these more challenging approaches by providing a virtual digital "surgical exposure". We have explored areas of new endeavor that may not have current applications. We believe that this textbook will be attractive to those new to this area as well as providing an update for existing users. Readers will appreciate the international flavor of this textbook, each of our colleagues "speaks" in his own style. From the contents I) Computer assited orthopaedic surgery -- II) TKA -- IIA) navigation: TKA -- IIB) Minimally invasive surgery (MIS): TKA -- IIC) MIS and navigation in TKA -- IID) Navigation and MIS in unicompartmental knee arthroplasty (UKA) -- III) ACL reconstruction -- IV) Total hip arthroplasty -- IVA) Navigation: THA -- IVB) Minimally invasive surgery: THA -- IVC) Navigation and MIS: THA -- V) Reconstruction and trauma surgery -- VI) Spinal surgery -- VII) Future perspectives in CAOS.